A note on the weighted log canonical threshold of toric plurisubharmonic functions - Quy, Hoang Nhat (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 517.54 We prove a semicontinuity theorem for a class of certain weighted log canonical threshold of toric plurisubharmonic functions.